1996
DOI: 10.1063/1.360921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stoichiometry on the dynamic mechanical properties of LiNbO3

Abstract: Articles you may be interested inIntrinsic anomalous ferroelectricity in vertically aligned LiNbO3-type ZnSnO3 hybrid nanoparticle-nanowire arrays Appl. Phys. Lett. 105, 212903 (2014); 10.1063/1.4902557 40-50MHz lithium niobate (LiNbO3) transducers for pulsed Doppler measurements in mouse embryos Acoustic and optic phonons have been measured by Brillouin and Raman spectroscopies in LiNbO 3 samples with different stoichiometries. Consequently, the elastic constants have been determined by Brillouin scattering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…From these data, using best fit procedure with lorentzian curve to interpolate the data, we obtain line width parameters (reported in Table 1) for the above mentioned E and A modes. The values are very close to those reported in previous works [6][7][8] confirming nominal stoichiometry and evidencing a low structural disorder degree. In addition, at this amount, iron doping does not induce marked Raman modes broadening.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…From these data, using best fit procedure with lorentzian curve to interpolate the data, we obtain line width parameters (reported in Table 1) for the above mentioned E and A modes. The values are very close to those reported in previous works [6][7][8] confirming nominal stoichiometry and evidencing a low structural disorder degree. In addition, at this amount, iron doping does not induce marked Raman modes broadening.…”
Section: Resultssupporting
confidence: 92%
“…In LN the line width of some Raman lines (E(TO) mode at ∼150cm -1 and A 1 mode at ∼ 870cm [6][7][8]. Additional information about disorder arising in the ferroelectric chains Nb-O can be obtained from weak and broadened features in the spectra between 550-800cm -1 [9,10].…”
Section: Resultsmentioning
confidence: 97%
“…For example, the lowest soft A 1 1 mode was suggested being sensitive to Nb-site defect, while the A 2 1 mode being sensitive to the imperfection of Li-site. In addition, the A 4 1 mode was found to consist of three lines, which have been attributed to Nb vacancy V Nb -O, normal Nb-O and Nb Li -O bonds, respectively [17]. From Fig.…”
Section: Ag In Ln Lattice Structurementioning
confidence: 97%
“…The fitted peaks are labeled in Fig. 3 according to the Raman peak assignment reported before [16,17], and the fitted parameters are listed in Table 1.…”
Section: Ag In Ln Lattice Structurementioning
confidence: 99%
“…It has been demonstrated that the linewidth of some Raman lines can be correlated to the composition x c = [Li/(Li+ Nb)] of the LiNbO 3 crystal [7][8][9]. In addition, Raman data have also been utilized to elucidate the mechanism of Mg ion incorporation in the defective LN lattice or the role of H in disordering the ferroelectric chain Nb-O after proton exchange [10,11].…”
mentioning
confidence: 97%